GSK3β Modulates Timing-Dependent Long-Term Depression Through Direct Phosphorylation of Kv4.2 Channels. (23rd February 2018) - Aceto, Giuseppe; Re, Agnese; Mattera, Andrea; Leone, Lucia; Colussi, Claudia; Rinaudo, Marco; Scala, Federico; Gironi, Katia; Barbati, Saviana Antonella; Fusco, Salvatore; Green, Thomas; Laezza, Fernanda; et al.
Abstract: Spike timing-dependent plasticity (STDP) is a form of activity-dependent remodeling of synaptic strength that underlies memory formation. Despite its key role in dictating learning rules in the brain circuits, the molecular mechanisms mediating STDP are still poorly understood. Here, we show that spike timing-dependent long-term depression (tLTD) and A-type K + currents are modulated by pharmacological agents affecting the levels of active glycogen-synthase kinase 3 (GSK3) and by GSK3β knockdown in layer 2/3 of the mouse somatosensory cortex. Moreover, the blockade of A-type K + currents mimics the effects of GSK3 up-regulation on tLTD and occludes further changes in synaptic strength. Pharmacological, immunohistochemical and biochemical experiments revealed that GSK3β influence over tLTD induction is mediated by direct phosphorylation at Ser-616 of the Kv4.2 subunit, a molecular determinant of A-type K + currents. Collectively, these results identify the functional interaction between GSK3β and Kv4.2 channel as a novel mechanism for tLTD modulation providing exciting insight into the understanding of GSK3β role in synaptic plasticity.